NH Fuse Maintenance for Low Voltage Network Protection: Perawatan Sekring NH untuk Perlindungan Jaringan Tegangan Rendah - Firmansyah, Fikri Alam; Anshory, Izza (Universitas Muhammadiyah Sidoarjo, 2024)
This study presents an analysis of NH replacement in the low voltage network, focusing on the XYZ region. NHs, integral safety devices within the distribution system, are subject to replacement when they exceed their useful life limit or incur damage. Through low voltage network analysis, this research identifies network conditions and potential interferences, facilitating targeted NH replacement to uphold network reliability. The study highlights the importance of NH replacement in minimizing disruptions and preventing NH damage, thereby enhancing overall network resilience. Highlights : NH replacement ensures safety and reliability: Regular replacement of NHs within the low voltage network minimizes potential disruptions and safeguards against electrical disturbances. Targeted replacement strategies: Utilizing network analysis, NH replacement is conducted based on factors such as useful life limit exceedance and damage, optimizing network performance. Enhanced network resilience: By mitigating potential disruptions and preventing NH damage, replacement initiatives contribute to the overall reliability and resilience of the low voltage network. Keywords: NH replacement, low voltage network, reliability, analysis, maintenance